Clonal haematopoiesis as a risk factor for therapy‐related myeloid neoplasms in patients with chronic lymphocytic leukaemia treated with chemo‐(immuno)therapy. (11th March 2022) - Voso, Maria‐Teresa; Pandzic, Tatjana; Falconi, Giulia; Denčić‐Fekete, Marija; De Bellis, Eleonora; Scarfo, Lydia; Ljungström, Viktor; Iskas, Michail; Del Poeta, Giovanni; Ranghetti, Pamela; Laidou, Stamatia; Cristiano, Antonio; et al.
Abstract: Clonal haematopoiesis of indeterminate potential (CHIP) may predispose for the development of therapy‐related myeloid neoplasms (t‐MN). Using target next‐generation sequencing (t‐NGS) panels and digital droplet polymerase chain reactions (ddPCR), we studied the myeloid gene mutation profiles of patients with chronic lymphocytic leukaemia (CLL) who developed a t‐MN after treatment with chemo‐(immuno)therapy. Using NGS, we detected a total of 30 pathogenic/likely pathogenic (P/LP) variants in 10 of 13 patients with a t‐MN (77%, median number of variants for patient: 2, range 0–6). The prevalence of CHIP was then backtracked in paired samples taken at CLL diagnosis in eight of these patients. Six of them carried at least one CHIP‐variant at the time of t‐MN (median: 2, range: 1–5), and the same variants were present in the CLL sample in five cases. CHIP variants were present in 34 of 285 patients from a population‐based CLL cohort, which translates into a significantly higher prevalence of CHIP in patients with a CLL who developed a t‐MN, compared to the population‐based cohort (5/8, 62.5% vs. 34/285, 12%, p  = 0.0001). Our data show that CHIP may be considered as a novel parameter affecting treatment algorithms in patients with CLL, and highlight the potential of using chemo‐free therapies in CHIP‐positive cases.